A Study of Interest Rate Thresholds on Foreign Investment in the Construction Sub-Sector in Indonesia - Lumintang, Zulfikar Halim; Damayanty , Prisila; Mubarok, Faizul (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The construction subsector plays a strategic role in driving infrastructure development, regional connectivity, and national economic competitiveness. However, the realization of foreign direct investment (FDI) in this subsector remains relatively low compared to other sectors, despite the improving investment climate in Indonesia. One of the main factors influencing foreign investors’ decisions is macroeconomic variables such as interest rates, exchange rates, and foreign reserves, which in the context of the construction subsector are suspected to have a complex and not entirely linear relationship. This study aims to analyze the realization of FDI in the construction subsector along with the macroeconomic factors affecting it, to identify the nonlinear relationship pattern between interest rates and FDI, and to estimate the optimal interest rate threshold to attract foreign investment. The research uses quarterly secondary data from 2010–2023, analyzed with the Vector Error Correction Model (VECM), supported by RESET test, Johannsen cointegration, IRF, and FEVD. The results reveal a nonlinear inverted U-shaped relationship between interest rates and FDI in the construction subsector, with an optimal threshold at 4.195%. At moderate levels, interest rates have a significant positive effect, but become negative when exceeding this optimal point. Conversely, exchange rates and foreign reserves do not significantly affect FDI, although their directional relationships are consistent with theoretical expectations. These findings suggest that prudent interest rate management, exchange rate stability, and structural improvements in the construction subsector are crucial to enhancing Indonesia’s attractiveness to foreign investors.